GLOBAL PERSPECTIVES ON AGING WITH HIV AND INSIGHTS FROM UKRAINE (REVIEW OF THE BOOK “HIV, SEX, AND SEXUALITY IN LATER LIFE”) - SLOZANSKA, Hanna (Social work and education, 2024)
In the wake of the ongoing global viral pandemic, the profound impact of COVID-19 has highlighted the resilience and adaptability of global health infrastructures. However, as we navigate these challenging times, the book "HIV, Sex, and Sexuality in Later Life" (Henrickson et al., 2022) was published by Policy Press, Bristol, UK. It redirects our attention to the enduring and intersectional challenges faced by individuals living with HIV, particularly as they age. The book reflects on the unimaginable notion of chronicling the lives of older individuals living with HIV, a concept deemed unthinkable during the early years of the pandemic. The resilience of individuals, coupled with advancements in research and technology, has defied expectations, allowing people to live longer lives with HIV, even in resource-scarce environments.